Operationalizing the HIV prevention cascade for PWID using the integrated bio‐behavioural survey data from Ukraine - Dumchev, Kostyantyn (J Int AIDS Soc, 2020)
INTRODUCTION: People who inject drugs (PWID) remain at high risk of HIV in many countries. The HIV prevention cascades have been proposed to replicate the success of the treatment cascades and reinvigorate the prevention programmes through improved monitoring, planning and delivery. We adapted the cascade framework to the PWID context in Ukraine, assessed gaps and analysed factors associated with achieving “access” and “effective use” outcomes. METHODS: Self‐reported data on the use of prevention services and risk behaviours from the 2017 integrated bio‐behavioural survey among PWID in Ukraine were used to construct cascades for needle/syringe and condom programmes (NSP and CP). Socio‐demographic and behavioural variables were evaluated as potential correlates of cascade outcomes. RESULTS: The NSP cascade analysis included 7815 HIV‐negative PWID. Motivation to use clean syringes was not assessed and assumed at 100%. Access to clean syringes through NSP in the past 12 months was reported by 2789 participants (35.7%). Effective use of syringes (no sharing in the past 30 days) was reported by 7405 participants (94.8%). NSP access was higher among women, individuals older than 44, and mixed drug users; while effective use was reported more frequently by men and opioid users, with no difference by age. The CP cascade analysis included 6606 (85%) of the HIV‐negative PWID who had sex in the past three months. Of those, 2282 (34.5%) received condoms, and 1708 (25.9%) reported consistent use with all partners in the past three months. Older PWID and mixed‐drug users accessed condoms more frequently; whereas younger subgroups and opioid users used them more consistently. CONCLUSIONS: Overall, the cascade framework was useful to describe the status of HIV prevention among PWID in Ukraine and to identify areas for improvement in the programming and evaluation of HIV prevention. Access to needle/syringe and condom programmes was substantially below the recommended levels. Effective use of clean syringes was reported by a vast majority of PWID, although likely affected by self‐report bias; whereas consistent condom use was infrequent. Socio‐demographic and behavioural variables showed significant associations in NSP and CP cascade analyses, with little consistency between the access and effective use outcomes.